Fusarium root rot caused by Fusarium solani on sweet potato (Ipomoea batatas) in South Korea. Issue 1 (2nd January 2018) - Yang, Jung-Wook; Nam, Sang-Sik; Lee, Hyeong-Un; Choi, Kyu-Hwan; Hwang, Se-Gu; Paul, Narayan Chandra
Abstract: Fusarium species are important post-harvest pathogens of sweet potato worldwide. A root rot disease was observed on sweet potato ( Ipomoea batatas ) at storage houses in different locations in South Korea during 2016–2017. The disease was characterized by circular lesions with dark and light brown concentric rings along with cavities in the inner part of the root. Seven isolates were recovered from diseased samples. Two representative isolates were cultured on potato dextrose agar and the morphology was studied. Macroconidia were cylindrical and slightly curved with blunt and rounded apical cells. The size of the macroconidia was 28.3 (15.0–44.3) × 5.8 (4.2–8.3) μm. The microconidia were fusiform to ovoid, variable in size and aseptate or rarely with single septa. Microconidial size varied from 9.2 (5.2–16.1) × 3.6 (2.6–4.5) μm. The fungal isolates were identified as Fusarium solani (Martius) Appel & Wollenweber emend. Snyder & Hansen on the basis of the morphological and cultural characteristics. The isolates were confirmed as F. solani on the basis of molecular identification by rDNA–ITS and translation elongation factor (EF 1-α) gene sequence analysis. The pathogenicity of the organism was confirmed by fulfilling Koch's postulates. To our knowledge, this is the first report of F. solani root rot of sweet potato in South Korea.